The Juridical Analysis of the Use of Electronic Signatures on Electronic Land Certificates in the Conception of Legal Certainty - Abdullah Galih Nanda Prasetya; Bambang Tri Bawono (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to analyze: 1) Juridical analysis of the use of electronic signatures on electronic land certificates in the conception of legal certainty. 2). Legal protection for electronic certificate holders as a guarantee of ownership of land rights. The approach method used in discussing this research problem is a normative juridical approach. The specification of the research used is descriptive analytical research. This type of data uses secondary data. The data analysis method used in this research is qualitative data analysis. The results of the study concluded: 1) The use of electronic signatures on electronic land certificates in the conception of legal certainty is legal and can be used as authentic evidence if needed in court. The use of electronic signatures on electronic land certificates guarantees legal certainty for land owners. The use of electronic signatures in court is a form of expansion of valid evidence in accordance with the applicable procedural law in Indonesia. An electronic signature has the same proving power as an authentic deed. As stipulated in the ITE Law, Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 3 of 2019 and Spatial Planning/Head of National Land Agency of the Republic of Indonesia Number 1 of 2021. 2) Legal protection for electronic certificate holders as a guarantee of ownership of land rights is guaranteed by law. Repressive protection regarding electronic land certificates, as evidence of electronic ownership is recognized by the Electronic Information and Transaction Law (UU ITE). In terms of validity, there are no problems, especially since it has been strengthened in Article 5 of the Ministerial Regulation of ATR/BPN No. 1 of 2021, as well as Article 84 of Government Regulation No. 18 of 2021. Meanwhile, preventive protection for security has been prepared by the Ministry of ATR/BPN in anticipation of data leakage through collaboration with BSSN. . The electronic land certificate will enforce an electronic signature and use a Hash Code (a method to verify authenticity) and a QR Code (a matrix code created so that its contents can be parsed at high speed which requires a scan or scan to open it) guaranteed by the National Cyber and Crypto Agency (BSSN).